Caregiving for Patients With Frontotemporal Dementia in Latin America - Piña-Escudero, Stefanie Danielle; Aguirre, Gloria Annette; Javandel, Shireen; Longoria-Ibarrola, Erika Mariana (Frontiers in Neurology, 2021)
Latin America is a vast heterogeneous territory where chronic diseases such as mild cognitive impairment or dementia are becoming higher. Frontotemporal dementia (FTD) prevalence in this region is estimated to be around 12–18 cases per thousand persons. However, this prevalence is underestimated given the lack of awareness of FTD even among healthcare professionals. Family members are responsible for the care of patients with FTD at home. These caregivers deliver care despite being ill-equipped and living in the context of austerity policies and social inequities. They often face unsurmountable financial and social burdens that are specific to the region. The most important step to support caregivers in Latin America is to increase awareness of the disease at all levels. Healthcare diplomacy is fundamental to create joint efforts that push policies forward to protect caregivers of FTD patients.